POLA KOORDINASI PEMERINTAH DESA DENGAN MASYARAKAT DALAM UPAYA PENCEGAHAN PERNIKAHAN DINI DI DESA PANTUNGO KECAMATAN TELAGA BIRU - Pakudu, Robin (STISIPOL Mujahidin Buol, 2024)
This research aims to provide an overview of coordination patterns in efforts to prevent early marriage at the Pantungo Village office, Telaga Biru District, Gorontalo Regency. The research method used is qualitative with a descriptive approach. Data collection techniques are carried out through interviews, observation and documentation. The results show that the pattern of coordinating unified action in efforts to prevent early marriage in Pantungo Village is not yet fully optimal because the relevant parties are still implementing their respective programs. Currently, the relationship between the village government, community and other related parties is still in the communication stage because it is not clear in the regional regulations or village regulations who is responsible for coordinating. So far, the village government has only carried out efforts to prevent early marriage as a moral burden and in the context of community development. However, the pattern of communication coordination in efforts to prevent early marriage in Pantungo Village is optimal. The village government provides advice and guidance to the community, as well as religious counselors through outreach on Islamic holidays and at marriage advice events. Even though it is not yet well coordinated, the coordination pattern in the division of labor is optimal, where parents are fully responsible if early marriage occurs. However, as a moral burden, each relevant party carries out their respective roles. Apart from that, the discipline coordination pattern is also not optimal, where parents are fully responsible, and there is no commitment from the village government to coordinate related parties in efforts to prevent early marriage.